If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 75 + -3x = 33x + 23 Reorder the terms: 75 + -3x = 23 + 33x Solving 75 + -3x = 23 + 33x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33x' to each side of the equation. 75 + -3x + -33x = 23 + 33x + -33x Combine like terms: -3x + -33x = -36x 75 + -36x = 23 + 33x + -33x Combine like terms: 33x + -33x = 0 75 + -36x = 23 + 0 75 + -36x = 23 Add '-75' to each side of the equation. 75 + -75 + -36x = 23 + -75 Combine like terms: 75 + -75 = 0 0 + -36x = 23 + -75 -36x = 23 + -75 Combine like terms: 23 + -75 = -52 -36x = -52 Divide each side by '-36'. x = 1.444444444 Simplifying x = 1.444444444
| W^2+3=7w | | -(7y+1)-(6y-8)=7 | | a^2+6a=-3 | | 13-9x=106-30x | | 0.60x+.05(2-x)=.10(-98) | | -156-10=8x+24 | | 2(8s+5)-6s=2(5s+3)-7 | | 16x^2-19x+18=0 | | -2p+8=5-(7p+4) | | 3x+7=8x+13 | | 11x+=5x+37 | | 0.3(x+70)+1.5x=102 | | 3+p=9 | | -(3y+4)-(-2y-7)=-2 | | 144x^2-169y^2=0 | | 0.70x+.05(6-x)=.10(16) | | 8x^2+11xy+3y^2=0 | | x+12y+11x-13y-9= | | 8(x+5)=4(2x+3)+28 | | 4x-17=(3x-2)*4 | | 3x-3=7x+12 | | 4x=3y | | 3x-3=7x-12 | | 9x+5-4x-3+x=146 | | 2-6t-9-2t= | | -6-(2-3p)= | | -8n-9+7n= | | -[2z-(11z+1)]=1+(8z+6) | | x*0.1=20 | | -2z+11z+1=8z+6 | | 0.55x+.05(8-x)=.10(64) | | 20*x=0.1 |